Wide-Bandgap All-Inorganic CsPbIBr2 Top Cells With MoOx/Ag/TeO2 Composite Transparent Anode Towards Efficient Four-Terminal Perovskite/Si Tandem Solar Cells - Fengqin He; Wuxiong Fei; Yilin Wang; Chenbo Liu; Qirui Guo; Wensheng Lan; Gang Fan; Gang Lu; Dazheng Chen; Weidong Zhu; He Xi; Chunfu Zhang (IEEE Photonics Journal, 2021)
Wide-bandgap all-inorganic CsPbIBr2 solar cells with MoOx/Ag/TeO2 composite transparent electrode have been firstly used to construct a 4T perovskite/Si-heterojunction tandem cells. The calculation results showed that the long wavelength transmission (600 to 1100 nm) of MoOx/Ag film can be enhanced remarkably by adding a TeO2 optical capping layer. This resulted in an obviously increase of the PCE (JSC) from 10.70% (17.56 mA/cm2) to 14.76% (24.67 mA/cm2) for corresponding bottom Si cell in CsPbIBr2/Si devices, although the PCE of top CsPbIBr2 cell decreased from 17.52% to 16.58%, the overall PCE of tandem device has increased from 28.22% to 31.34%. This JSC-dependent PCE improvement mainly came from the more balanced light absorption, which can be understood by the optical interference induced light field redistributions in CsPbIBr2/Si devices. Specially, comparing with the original Si cell, the JSC and PCE losses in bottom Si cell have been suppressed to about 33% and 32%, which are superior to most the reported pervoskite/Si tandem cells. Therefore, the tandem of Si cell and CsPbIBr2 cell with optimized MoOx(20 nm)/Ag(8 nm)/TeO2(50 nm) transparent electrode could be the promising cost-effective photovoltaic in the future. This work is instructive to the fabrication of pervoskite/Si tandem solar cells.